Structure and properties of FeCr, CrAl and FeCrAl coatings deposited by cathodic arc evaporation - Vasilenko, R.L.; Voyevodin, V.N.; Belous, V.А.; Bortnitskaya, М.A.; Kolodiy, І.V.; Klimenko, І.О.; Ovcharenko, V.D.; Kovalenko, V.І.; Marinin, V.G.; Ilchenko, A.V.; Tikhonovsky, М.А.; Kuprin, A.S. (Вопросы атомной науки и техники, 2021)
Protective coatings with different compositions of Fe, Cr, and Al were deposited by cathodic arc evaporation method on fragments of Zr1Nb alloy fuel claddings. The influence of the composition and structural state of the developed coatings on their physical and mechanical properties (microhardness, resistance to corrosion and cavitation and abrasive wear) has been studied. It is shown that the optimal combination of mechanical properties and high resistance to oxidation from a series of studied coatings FeCr, FeCrAl, and CrAl have coatings of the FeCrAl system with a concentration of Cr ⁓ 22 at.% and Al ⁓ 14.3 at.%. It was found that protective coatings such as FeCr, FeCrAl, and CrAl with a thickness of ⁓ 12 μm significantly increase the resistance to oxidation and prevent the destruction of fuel claddings under oxidation in air at a temperature of 1150 °C for 1 h.